PROFITABILITY RATIOS AND STOCK PRICES: EMPIRICAL EVIDENCE ON THE BUILDING CONSTRUCTION SUBSECTOR - Waluyo, Louis; Widianingsih, Luky Patricia (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2020)
Capital market is a place for various parties to conduct buy and sell transactions of shares and/ or bonds aiming for additional funds, strengthen company’s capital and investment. Among all the instruments sold in the capital market, stocks are one of the most demanded products by prospective investors. A country’s stock price movement can be used as a reference to see how the country’s economic policies are running. This research aims to analyze the impact of NPM, GPM, EPS, ROA, and ROE on stock price of the building construction subsector. This research uses secondary data of companies’ annual financial report. Population in this research are a building construction subsector listed on the Indonesia Stock Exchange on 2014-2017 which is 16 companies. Based on purposive sampling method, a research sample of 9 companies are obtained. This research analysis technique uses multiple linear regression analysis by using SPSS 24. The result showed that NPM and ROE have positive influence on stock price, ROA has negative influence on stock price, whereas GPM and EPS have no influence on stock price, whereas GPM and EPS have no influence on stock price. The coefficient of adjusted R2 is 36.9% meaning 36.9% of the stock price as dependent variable is influenced by NPM, GPM, EPS, ROA, and ROE, while the remaining 63.1% is influenced by other variables outside this research model.